2009
DOI: 10.1017/s0033291709990833
|View full text |Cite
|
Sign up to set email alerts
|

The pattern and course of cognitive impairment in late-life depression

Abstract: Cognitive deficits in late-life depression persist up to 4 years, affect multiple domains and are related to trait rather than state effects. Differences in severity and course between early and late onset depression suggest different pathogenic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
94
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 49 publications
16
94
1
6
Order By: Relevance
“…We hypothesized that similar changes in the glutamatergic pyramidal neurons (Kirvell et al, 2010) in layers III (which largely project within the neocortex) and V (which make up the frontal circuits and connect to subcortical pathways to the basal ganglia and thalamus) (Tekin and Cummings, 2002;) may relate to executive dysfunction in dementia caused by cerebrovascular disease (Allan et al, 2011). We and others (Cotter et al, 2005;Rajkowska et al, 2005; have reported layer-specific reductions in pyramidal neurons of older depressed subjects, a syndrome postulated to have its basis in frontal vascular pathology (Alexopoulos et al, 1997;Ongur et al, 1998;Thomas et al, 2004;Kohler et al, 2010). Thus the question arises whether there is a similar global loss in post-stroke dementia, in which depression is also manifested (Altieri et al, 2012;Allan et al, 2013).…”
Section: Introductionmentioning
confidence: 84%
“…We hypothesized that similar changes in the glutamatergic pyramidal neurons (Kirvell et al, 2010) in layers III (which largely project within the neocortex) and V (which make up the frontal circuits and connect to subcortical pathways to the basal ganglia and thalamus) (Tekin and Cummings, 2002;) may relate to executive dysfunction in dementia caused by cerebrovascular disease (Allan et al, 2011). We and others (Cotter et al, 2005;Rajkowska et al, 2005; have reported layer-specific reductions in pyramidal neurons of older depressed subjects, a syndrome postulated to have its basis in frontal vascular pathology (Alexopoulos et al, 1997;Ongur et al, 1998;Thomas et al, 2004;Kohler et al, 2010). Thus the question arises whether there is a similar global loss in post-stroke dementia, in which depression is also manifested (Altieri et al, 2012;Allan et al, 2013).…”
Section: Introductionmentioning
confidence: 84%
“…State effects are expected to be present only during the clinical depressive episode, while trait effects are expected to endure after depressive symptoms have resolved. In a recent study, Koehler and colleagues [27] examined older subjects with and without MDD, and found that tests of global cognition, memory, executive functioning, and processing speed did not differ significantly when mood, remission status, or antidepressant treatment were taken into account. The authors concluded that cognitive deficits in late-life depression persist over months to years, affect multiple domains, and are a manifestation of trait rather than state effects of depression.…”
Section: Discussionmentioning
confidence: 99%
“…20 As per newer studies, approximately half of the patients with late-onset depression have generalized cognitive impairment. 21 Symptoms of depression are often precursors of cognitive decline 22 and dementia 23 with senior individuals who have major depression and neurocognitive impairment likely to develop major neurocognitive impairments within a few years of onset of depression. 24,25 Symptoms of depression in early years are also a potential risk factor for disorders of dementia.…”
Section: Neurologic or Psychiatric Comorbiditiesmentioning
confidence: 99%